Characterization of adhesion properties of the cardiomyocyte integrins and extracellular matrix proteins using atomic force microscopy. Issue 4 (11th November 2019) - Li, Zecheng; Liu, Tianqi; Yang, Junxian; Lin, Jiangguo; Xin, Sherman Xuegang
Abstract: Integrins are transmembrane adhesion receptors that play important roles in the cardiovascular system by interacting with the extracellular matrix (ECM). However, direct quantitative measurements of the adhesion properties of the integrins on cardiomyocyte (CM) and their ECM ligands are lacking. In this study, we used atomic force microscopy (AFM) to quantify the adhesion force (peak force and mean force) and binding probability between CM integrins and three main heart tissue ECM proteins, ie, collagen (CN), fibronectin (FN), and laminin (LN). Functionalizing the AFM probes with ECM proteins, we found that the peak force (mean force) was 61.69 ± 5.5 pN (76.54 ± 4.0 pN), 39.26 ± 4.4 pN (59.84 ± 3.6 pN), and 108.31 ± 4.2 pN (129.63 ± 6.0 pN), respectively, for the bond of CN‐integrin, FN‐integrin, and LN‐integrin. The binding specificity between CM integrins and ECM proteins was verified by using monoclonal antibodies, where α10 ‐ and α11 ‐integrin bind to CN, α3 ‐ and α5 ‐integrin bind to FN, and α3 ‐ and α7 ‐integrin bind to LN. Furthermore, adhesion properties of CM integrins under physiologically high concentrations of extracellular Ca 2+ and Mg 2+ were tested. Additional Ca 2+ reduced the adhesion mean force to 68.81 ± 4.0 pN, 49.84 ± 3.3 pN, and 119.21 ± 5.8 pN and binding probability to 0.31, 0.34, 0.40 for CN, FN, and LN, respectively, whereas Mg 2+ caused very minor changes to adhesion properties of CM integrins. Thus, adhesion properties between adult murine CM integrins and its main ECM proteins were characterized, paving the way for an improved understanding of CM mechanobiology. Abstract : The cardiomyocytes primarily express integrins that bind to three main extracellular matrix proteins in heart tissues including collagen, fibronectin, and laminin. To quantify the difference of the interactions between cardiomyocyte integrins and these three extracellular matrix proteins in heart tissues, we used atomic force microscopy to quatify the adhesion properties of the interactions in molecular level.